PERBANDINGAN MODEL PEMBELAJARAN STAD, TGT, DAN KOMBINASI STAD-TGT DALAM MENINGKATKAN HASIL BELAJAR SISWA TKR KELAS XI PADA MATA PELAJARAN PKKR - Bunga Rahmania; Ikhsanudin; Sulaeman Deni Ramdani (Universitas Negeri Surabaya, 2023)
This study is aiming to compare learning achievement of the students with the STAD, TGT, and STAD-TGT combination models. This research is quasi-experimental research. The samples used were 3 classes from SMKN 1 Ciruas and SMK PGRI 1 Serang. Data collection using test and observation sheets of student activity. Data analysis techniques used descriptive analysis, normality test and homogeneity test, as well as hypothesis testing. The results of the study were obtained through descriptive analysis with an average learning achievement using the STAD model is 58.33, TGT model is 54.47, and STAD-TGT combination model is 65.29. Descriptively, the learning achievement category in STAD-TGT combination model is higher than two other models. Based on the descriptive analysis it was concluded that the learning outcomes of the STAD-TGT combination model obtained the highest average score. However, this difference was not significant, as evidenced by the Tukey HSD test which resulted in the STAD-TGT combination model with the STAD model (sig. 0.447), while the difference occurs significantly between the STAD-TGT combination model and the TGT model (sig. 0.027). The conclusion in this study is that the STAD-TGT combination model is sequentially better in improving student learning outcomes in class XI TKR. Keywords: experiment; learning acheivement; STAD, TGT, STAD-TGT combination.